The Effect of Tax Extensification, Taxpayer Behavior Control and Tax Counseling on Individual Taxpayer Compliance Moderated by Tax Amnesty at KPP Pratama Medan Polonia - Friskacindy Wilya Shinta Gulo; Heriyati Chrisna; Nina Andriany Nasution (Yayasan Multidimensi Kreatif, 2025)
This study aims to determine and analyze the effect of tax extensification, taxpayer behavioral control and tax counseling on individual taxpayer compliance moderated by tax amnesty at KPP Pratama Medan Polonia. This study uses primary data by distributing questionnaires via google form to individual taxpayers registered at KPP Pratama Medan Polonia. The total population in this study was 237,168 taxpayers. Sampling was carried out using the slovin formula so that a sample of at least 100 taxpayers was obtained. The data analysis techniques used are multiple linear regression analysis and Moderated Regression Analysis (MRA). The results of the study indicate that simultaneously tax extensification, taxpayer behavioral control and tax counseling have a significant effect on individual taxpayer compliance in Pratama Medan Polonia. Partially, taxpayer behavioral control and tax counseling have a positive and significant effect on individual taxpayer compliance. While the tax extensification variable has no effect on individual taxpayer compliance. For tax amnesty as a moderating variable, it cannot strengthen the effect of tax extensification, taxpayer behavioral control and tax counseling on individual taxpayer compliance.